Systemic Sarcoidosis Presenting in a Scar - Amy Xiao; Lauryn M. Falcone; Joseph C. English III (Hindawi Limited, 2023)
While most forms of sarcoidosis of the skin do not require treatment, 40% of patients initially diagnosed with cutaneous sarcoidosis are found to have an asymptomatic disease involving other organ systems. It is the involvement of the lungs, heart, eyes, and nervous system which most often contributes to morbidity/mortality. An early and accurate diagnosis of sarcoidosis is difficult because patients may be asymptomatic, initial presentations may vary, and there is no single reliable diagnostic test except biopsy. We present a case of scar sarcoidosis which led to the diagnosis of stage II pulmonary sarcoidosis in a woman in her 50s. Her scar sarcoidosis presented as well-circumscribed, reddish-brown macules surrounding an atrophic scar from a prior skin graft on the right leg. Biopsy revealed scattered, well-formed, non-necrotizing granulomas of the dermis composed of epithelioid histiocytes and multinucleated giant cells, surrounded by a sparse infiltrate of lymphocytes and histiocytes. A CT chest demonstrated extensive hilar lymphadenopathy, leading to a diagnosis of stage II pulmonary sarcoidosis with cutaneous involvement. This case illustrates the interesting presentation of scar sarcoidosis and underscores the importance of a broad differential including sarcoidosis for skin changes around scars and underscores the need for early biopsy. Prompt cutaneous diagnosis leads to earlier systemic evaluation, therapeutics, and better outcomes.